2021
DOI: 10.1002/fsn3.2403
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the effects of inulin‐type fructan intake on body weight, blood glucose, and lipid profile: A systematic review and meta‐analysis of randomized controlled trials

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 94 publications
1
15
1
1
Order By: Relevance
“…In addition to the immunomodulatory effects of polysaccharides, specifically arabinoxylan, a previous study showed that they regulate the level of lipopolysaccharides in the blood in the case of high‐fat diets (Li et al., 2019). Moreover, inulin‐type fructan Wich is a prebiotic polysaccharide that increases HDL cholesterol, decreases LDL cholesterol, and lowers blood glucose and triglycerides in diabetics patients (Li et al., 2021).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the immunomodulatory effects of polysaccharides, specifically arabinoxylan, a previous study showed that they regulate the level of lipopolysaccharides in the blood in the case of high‐fat diets (Li et al., 2019). Moreover, inulin‐type fructan Wich is a prebiotic polysaccharide that increases HDL cholesterol, decreases LDL cholesterol, and lowers blood glucose and triglycerides in diabetics patients (Li et al., 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, inulin-type fructan Wich is a prebiotic polysaccharide that increases HDL cholesterol, decreases LDL cholesterol, and lowers blood glucose and triglycerides in diabetics patients (Li et al, 2021).…”
Section: Analysis Of Microbial Communities With Different Substratesmentioning
confidence: 99%
“…The dosages and durations of dietary fiber intervention ranged from 3 g/day to 30 g/day (except for one study, which used guar gum at 15 mg/day, and another study that used brown rice at 225 g/d), and 4 to 13 weeks, respectively. Twenty-two meta-analyses were performed in China ( 23 , 25 27 , 29 31 , 35 37 , 42 , 43 , 45 , 49 , 51 , 53 56 , 69 71 ), six in Iran ( 24 , 32 34 , 38 , 40 ), four in the UK ( 13 , 39 , 41 , 57 ), one in Australia ( 14 ), eight in Canada ( 44 , 46 , 47 , 50 , 52 , 58 , 62 , 72 ), five in the USA ( 48 , 60 , 65 , 67 , 68 ), one in Brazil ( 59 ), one in Ireland ( 61 ), one in South Africa ( 63 ), one in Italy ( 64 ), one in the Netherlands ( 66 ), and one in Malaysia ( 28 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, a recent systematic review with 27 probiotic interventions (Lactobacillus, Bifidobacterium, Clostridium and Akkermansia) reported contradictory results regarding the effects of certain probiotics on amelioration of IR, suggesting the need for long-term RCTs in people with obesity and cardiometabolic risk [410]. Results from two systematic reviews and meta-analyses of 33 RCTs in healthy, overweight/obese, prediabetes, T2DM, and hyperlipidemic subjects examining the metabolic effects of inulin-type fructan intake, reported a reduction in blood glucose, total cholesterol, and triglyceride concentrations in people with diabetes, although the mechanisms were inconclusive without differences from controls on body weight and blood insulin and with data showing large heterogeneity [411,412].…”
Section: Probiotic Dairy Foodsmentioning
confidence: 99%